P0061 Identification of CD44, α2β1-integrin, and CD133 expressing prostate cancer stem cells in patients from South Korea with prostate cancer. (July 2015) - Song, Y.S.; Lee, H.J.; Doo, S.H.; Kim, J.H.; Yang, W.J.
Abstract : Background: Existing therapies for prostate cancer eradicate most cells within a tumour. However, most patients develop androgen-independent disease that cannot be cured. Prostate cancer cells originate from rare stem cells responsible for maintenance of the tumour. Identification of a prostate cancer stem cell provides a useful target from which to develop therapies targeted at these stem cells. Methods: Four patients with prostate cancer were included. Their mean age was 72.3 (SD ± 6.6) years. PSA (ng/ml), Gleason score, node involvement, or metastasis in patients were recorded (88.1/7 [4+3], none or bone; 77.7/9 [5+4], iliac node, or bone; 31.4/9 [4+5], none or bone; 299/9 [5+4], iliac node or bone, respectively). Hormonal therapy of prostate cancer was given as a luteinising hormone-releasing hormone agonist and anti-androgen agent. A transurethral resection of the prostate was done and prostate tissue was obtained. Paraffin embedded serial sections (4 μm) were processed for prostate cancer tissue using immunofluorescent staining. Anti-CD133 antibody (1:10, clone 293C3), anti- α 2 β 1-integrin antibody (clone AK-7; TCS), and anti-CD44 (clone G44-26) were used to identify the prostate cancer cells. Stained sections of tissue were then examined under a Olympus laser confocal fluorescence microscope. Findings: CD44, α 2 β 1-integrin, and CD133 expressing cancer stem cells were randomly located throughout acini of prostate cancer. High levels of PSA, Gleason score, or lymph node involvement of prostate cancer was not predicted by the presence of cancer stem cells. Interpretation: We identified CD133, CD44, and α 2 β 1-integrin expressing cancer stem cells in patients in South Korea with prostate cancer.